Fungal Profile in Patients with Lung Cancer Receiving First-Line Chemotherapy - Faisal, Hana Khairina Putri; Aziziah, Aziziah; Pane, Irene Audrey Davalynn; Hasyim, Ammar Abdurrahman; Zaini, Jamal; Rozaliyani, Anna (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Patients with lung cancer are vulnerable to opportunistic infections, particularly fungal pulmonary infections such as those caused by Aspergillus spp., due to immunosuppression from both the disease and chemotherapy. Despite the clinical significance of these infections, data on their prevalence and associated factors in patients with lung cancer remain limited. This study aimed to determine the prevalence of Aspergillus spp. and identify associated factors in patients with lung cancer who underwent first-line chemotherapy at a national respiratory referral hospital in Indonesia. Methods: A cross-sectional study was conducted among 50 patients with lung cancer who had completed at least three cycles of chemotherapy. Sputum cultures were performed using Sabouraud dextrose agar (SDA), and serum immunoglobulin G (IgG) antibodies were tested using immunochromatographic assays. Demographic, clinical, and radiological data were collected. Bivariate and multivariate logistic regression analyses were used to identify factors associated with Aspergillus spp. infection. Results: Aspergillus spp. was detected in 92.0% of patients via sputum culture, with A. niger and A. fumigatus as the most common isolates. Over 30% showed co-colonization with other fungal species, such as Candida. Multivariate analysis revealed that a high Brinkman Index was independently associated with Aspergillus spp. colonization (p<0.05). Serum IgG antibody positivity was low (4%). Conclusion: There was a high prevalence of Aspergillus spp. colonization among patients with lung cancer undergoing chemotherapy, with smoking history emerging as a key risk factor. Targeted fungal screening is recommended, especially in heavy smokers, to facilitate early detection and improve outcomes.